2019
DOI: 10.3390/ijms21010122
|View full text |Cite
|
Sign up to set email alerts
|

HB-EGF Improves the Hair Regenerative Potential of Adipose-Derived Stem Cells via ROS Generation and Hck Phosphorylation

Abstract: Although adipose-derived stem cells (ASCs) have hair regenerative potential, their hair inductive capabilities are limited. The mitogenic and hair inductive effects of heparin binding-epidermal growth factor-like growth factor (HB-EGF) on ASCs were investigated in this study and the underlying mechanism of stimulation was examined. Cell growth, migration, and self-renewal assays, as well as quantitative polymerase chain reactions and immunostaining, were carried out. Telogen-to-anagen transition and organ cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…These effects can be enhanced by Ultraviolet B Preconditioning (2). Similar results were also achieved under the pretreatment of Minoxidil or cytokine (3,4). Dermal papilla cells (DPCs) lost their traits after culturing.…”
Section: Introductionsupporting
confidence: 62%
“…These effects can be enhanced by Ultraviolet B Preconditioning (2). Similar results were also achieved under the pretreatment of Minoxidil or cytokine (3,4). Dermal papilla cells (DPCs) lost their traits after culturing.…”
Section: Introductionsupporting
confidence: 62%
“…Ten studies evaluated the effect of MSC-CM on hair growth at the preclinical level (Park et al, 2010;Won et al, 2010Won et al, , 2015Dong et al, 2014;Shim, 2015;Choi et al, 2019;Gunawardena et al, 2019a;Ou et al, 2020;Xiao et al, 2020; Table 7). MSCs were isolated mainly from human hair follicles (Won et al, 2010;Won et al, 2015;Gunawardena et al, 2019a;Ou et al, 2020) (40%, 4/10) and human adipose tissue (Park et al, 2010;Choi et al, 2019;Xiao et al, 2020) (30%, 3/10). Other tissues used were human amniotic fluid , human deciduous teeth (Gunawardena et al, 2019a), human dermal cells (Shim, 2015), and murine bone marrow (Dong et al, 2014).…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…ROS is an important mediator of inflammation being secreted during wound healing and contributing to wound disinfection (Dunnill et al, 2017). It was shown that adipose-derived stem cells are also able to secrete ROS this way promoting DP-induced hair growth and thus, may cause TAT (Choi et al, 2019). However, in an in vivo study during the transition from anagen to catagen, Zhao and colleagues showed elevation of ROS level by the Foxp1 protein via suppression of ROS scavenger Thioredoxin-1.…”
Section: The Hf Cycle and Immunity In Physiological And Injury-inducementioning
confidence: 99%